Aid to fragile states: Do donors help or hinder? - Stephen Browne (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
he record of aid to fragile and poorly-performing states is the real test of aid effectiveness. Rich countries can justify aid to fragile states both through altruism and self-interest. But, with some exceptions, donors have appeared at the wrong times and with the wrong attitudes, even sometimes undermining development progress. State failure has dimensions of both will and capacity. Failure demands constructive engagement by donors, in some cases to save people in weak states from their leaders, and in all cases to save the states from circumstances which they cannot control. This paper examines the aid relationship with respect to three weak countries. Burma presents a case of comprehensive failure of political will and capacity, but isolating the regime, as some donors have chosen to do, will only perpetuate the plight of the population. Rwanda provides an alarming example of donor complicity in state collapse. The country has now rebounded from the terrible genocide of 1994, but some donors still cannot set aside their political and cultural biases. Zambia has lived through many years of bilaterally-assisted economic mismanagement, and also proved to be a highly unsuitable case for Bretton Woods treatment. It is doing better now that the country is more willing and able to take control of its development agenda. The paper concludes with eight principles for donors to observe in engaging more productively with fragile states.
Keywords: O19; F35; H56; O57; 330; fragile states; state failure; conflict; development aid; donors; donor coordination; capacity development; leadership; least developed countries; human development; Millennium Development Goals; Entwicklungshilfe; Staatskrise; Myanmar; Ruanda; Sambia